Spatiotemporal reconstruction of the Aquilegia rapid radiation through next‐generation sequencing of rapidly evolving cpDNA regions. Issue 2 (5th February 2013) - Fior, Simone; Li, Mingai; Oxelman, Bengt; Viola, Roberto; Hodges, Scott A.; Ometto, Lino; Varotto, Claudio
Summary: Aquilegia is a well‐known model system in the field of evolutionary biology, but obtaining a resolved and well‐supported phylogenetic reconstruction for the genus has been hindered by its recent and rapid diversification. Here, we applied 454 next‐generation sequencing to PCR amplicons of 21 of the most rapidly evolving regions of the plastome to generate c . 24 kb of sequences from each of 84 individuals from throughout the genus. The resulting phylogeny has well‐supported resolution of the main lineages of the genus, although recent diversification such as in the European taxa remains unresolved. By producing a chronogram of the whole Ranunculaceae family based on published data, we inferred calibration points for dating the Aquilegia radiation. The genus originated in the upper Miocene c . 6.9 million yr ago (Ma) in Eastern Asia, and diversification occurred c . 4.8 Ma with the split of two main clades, one colonizing North America, and the other Western Eurasia through the mountains of Central Asia. This was followed by a back‐to‐Asia migration, originating from the European stock using a North Asian route. These results provide the first backbone phylogeny and spatiotemporal reconstruction of the Aquilegia radiation, and constitute a robust framework to address the adaptative nature of speciation within the group.